The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1381/096089206777822142
|View full text |Cite
|
Sign up to set email alerts
|

Report of Two Cases of Gastric Cancer after Bariatric Surgery: Lymphoma of the Bypassed Stomach after Roux-en-Y Gastric Bypass and Gastrointestinal Stromal Tumor (GIST) after Vertical Banded Gastroplasty

Abstract: We report two new cases of gastric cancer diagnosed after a bariatric operation. The first case is a 66-year-old male who 3 years after gastric bypass suffered from a perforation of the fundus that was found to be secondary to a diffuse large B-cell lymphoma of the distal stomach. The second case is a 47-year-old woman who presented 12 years after a vertical banded gastroplasty with a gastric pouch outlet obstruction caused by a gastrointestinal stromal tumor (GIST). Based on the few reports of cancer in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 25 publications
0
37
0
4
Order By: Relevance
“…Several studies have reported that GIST-like pathologies may be detected during bariatric surgery procedures or postoperative histopathological examinations of the resected gastric specimen (4). A 57 years-old male patient was admitted to our clinics for a planned LSG due to morbid obesity.…”
Section: Dear Editormentioning
confidence: 99%
“…Several studies have reported that GIST-like pathologies may be detected during bariatric surgery procedures or postoperative histopathological examinations of the resected gastric specimen (4). A 57 years-old male patient was admitted to our clinics for a planned LSG due to morbid obesity.…”
Section: Dear Editormentioning
confidence: 99%
“…This is shown in the following case report: 23 A 47-year-old lady presented in our clinic after several months of progressive dysphagia with vomiting, 12 years after a VBG. These symptoms had been attributed to inadequate respect for dietetic rules after VBG.…”
Section: Gastric Cancer After Restrictive Operationsmentioning
confidence: 86%
“…22 The delay in diagnosis of cancer represents a risk for lesions arising in the excluded distal stomach that are more difficult to investigate. This is illustrated in the following case referred to our surgical department: 23 A 66-yearold male 3 years after RYGBP, was diagnosed with a gastric fundus perforation associated with a diffuse large B-cell lymphoma. The patient had a 6-month history of anemia with GI bleeds, with investigation by upper and lower endoscopy having been negative.…”
Section: Gastric Cancer In the Bypassed Stomach After Gastric Bypassmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48] However, it is probably that other cases have not been reported. An experimental study suggested that Roux-en-Y gastric bypass reduces the risk of development of gastric cancer due to the lack of contact of with carcinogens' lower bile reflux and fewer bacterial in the proximal gastric pouch.…”
Section: Discussionmentioning
confidence: 99%